Evaluation of platelet derived growth factor-BB levels in injectable platelet rich fibrin coated graft using gingival pedicle split thickness tunnel technique for isolated gingival recession: A randomized controlled trial - Leena Patil; M. Jayasheela; M.G. Triveni; G.V. Gayathri (Saudi Dental Journal)
Background: Use of injectable-platelet rich fibrin (i-PRF) in the field of periodontal regeneration is quite well known due to its efficacy. The study was aimed to evaluate the platelet derived growth factor-BB (PDGF-BB) levels in cases of isolated gingival recession using gingival pedicle split thickness tunnel technique (GPST) and de-epithelialized gingival graft (DGG) with or without coating it with i-PRF. Methodology: 20 patients exhibiting Miller’s class I/II isolated gingival recession were selected for this parallel arm randomized controlled trial. Recipient site was prepared using GPST technique, free gingival graft was harvested and de-epithelialized, further graft was coated with i-PRF and wound fluid samples from surgical site were collected at baseline, 3rd day and 7th day for group A. The same procedure without coating the graft in i-PRF was carried out for group B. Clinical parameters like probing depth, recession depth, recession width, width of keratinized gingiva, wound healing index (WHI), complete root coverage was recorded at baseline and after 4 months. Results: Significant intergroup difference was seen in WHI and the levels of PDGF-BB from baseline to the last estimated time point (p < 0.05). Conclusion: The study emphasizes on the use of novel GPST technique in conjunction with DGG coated with liquid PRF, which has shown sustained release of PDGF-BB resulting in better wound healing.